Fluorescence in situ hybridization of TP53 for the detection of chromosome 17 abnormalities in myelodysplastic syndromes. Issue 11 (2nd November 2015) - Sánchez-Castro, Judit; Marco-Betés, Víctor; Gómez-Arbonés, Xavier; García-Cerecedo, Tomás; López, Ricard; Talavera, Elisabeth; Fernández-Ruiz, Sara; Ademà, Vera; Marugan, Isabel; Luño, Elisa; Sanzo, Carmen; Vallespí, Teresa; et al.
Abstract : Conventional G-banding cytogenetics (CC) detects chromosome 17 (chr17) abnormalities in 2% of patients with de novo myelodysplastic syndromes (MDS). We used CC and fluorescence in situ hybridization (FISH) (LSI p53/17p13.1) to assess deletion of 17p in 531 patients with de novo MDS from the Spanish Group of Hematological Cytogenetics. FISH detected − 17 or 17p abnormalities in 13 cases (2.6%) in whom no 17p abnormalities were revealed by CC: 0.9% of patients with a normal karyotype, 0% in non-informative cytogenetics, 50% of patients with a chr17 abnormality without loss of 17p and 4.7% of cases with an abnormal karyotype not involving chr17. Our results suggest that applying FISH of 17p13 to identify the number of copies of the TP53 gene could be beneficial in patients with a complex karyotype. We recommend using FISH of 17p13 in young patients with a normal karyotype or non-informative cytogenetics, and always in isolated del(17p)